ANALISIS KEBIJAKAN LUAR NEGERI AMERIKA SERIKAT DALAM PENEMPATAN THAAD (TERMINAL HIGH ALTITUDE AREA DEFENSE WEAPON) DI KOREA SELATAN - Wibisono, Juwita Dewi Arimbi (Global and Policy Journal of International Relations, 2017)
ABSTRACTThis article explaining about the influence of national attributes in the foreign policy decision making process. Using proposition of Hudson, this article focuses on military and economic capabilities of the state. In this case, United States of America (USA) has been chosen as the best example because of two factors. First, USA known as an aggressive state. It can be seen in her involvement in some military show of force, such as deployment her THAAD (Terminal High Altitude Area Defense) system in South Korea to countervails North Korea. Second, USA had a great economic capability that used to support the development of their military capability. At last, the proposition that a great military and economic capabilities influence a more aggressive foreign policy is proven.Keywords: Military Capability, Economic Capability, Foreign Policy, Terminal High Altitude Area Defense, United States of America.